PENYEIMBANGAN BEBAN PADA JARINGAN TEGANGAN RENDAH GARDU DISTRIBUSI CD 33 PENYULANG SAWAH DI PT PLN (PERSERO) AREA BINTARO - Syarif Hidayat; Supridi Legino; Nurun Fatihah Mulyanti (Sekolah Tinggi Teknik - PLN, 2018)
The Power Distribution System is basically a process for delivering electricity from a 150 kV power transmission system to a consumer, either 20 kV consumer or a 380/220 V consumer. The more complex distribution system of the network is the Low Voltage distribution system (380 / 220V), because the network of low voltage distribution system has a very wide network coverage. This often causes the Low Voltage Distribution system to be unbalanced, since household customers generally utilize single phase power. The effects of an unbalanced low voltage distribution system will affect many things, such as : the transformer's performance, excess heat in the overload phase, the current flowing in the neutral wire, the end-tension drop in the overload load network. And ultimately the quality of electricity at the consumer level decreases. With this load imbalance, the workable solution is to balance the load on the transformer. The measurements of Jurusan B after load balancing are the R-phase 106 Ampere, the S-phase 108 Ampere, and the T-phase 107 Ampere. The load unbalance value drops to 1% after a load balancing effort, this value is far below the maximum imbalance criterion of 10%.